Imine-donor complexes with group 6 and group 11 transition metals : coordination and dynamics - De Jongh, Leigh-Anne (Stellenbosch : Stellenbosch University, 2008)
Thesis (MSc (Chemistry and Polymer Science))--Stellenbosch University, 2008.